Pathophysiological Reaction of the Body to Trauma: A Review Update - Talukder, Abdur Rabban; Quader, Feroze; Momen, MA (Journal of Science Foundation, 2016)
Trauma to tissues can be of large magnitude (macrotrauma), such as the trauma that exists with crush injuries and both moderate and severe sprains or strains. The trauma can also be of small magnitude (microtrauma), such as the trauma that typically exists with stress fractures and other overuse syndromes. Regardless of magnitude, trauma exists in several forms, including physical, chemical, thermal, metabolic, and biological. Injury from any of these sources induces an inflammatory response whose magnitude largely depends on the severity of the injury and the degree of vascularization of the tissue. A local inflammatory response always occurs in relation to trauma. Severe injury or multiple trauma evoke a systemic inflammatory response. This systemic inflammatory response to major injury is caused by hormonal, metabolic and immunological mediators, and is associated with a haemodynamic response. Accidental unanaesthetised trauma is also to a larger extent associated with ischemia, ischemia/reperfusion injury, hypovolemia and the immunological reactions secondary to blood transfusion. The systemic inflammatory response is required for tissue repair and has evolved in all mammals to optimize the healing potential of an organism. In uncomplicated trauma patients the systemic inflammatory response is temporary, predictable and well balanced between pro- and anti-inflammatory mediators. If the patient is exposed to severe major trauma an initial exaggerated proinflammatory response may be observed. In this review the pathophysiological changes have been described after trauma to the body. Journal of Science Foundation, 2015;13(1):15-20 DOI: http://dx.doi.org/10.3329/jsf.v13i1.27829